Indonesia Gold 2045 - Dedy Surahman; Ma’ruf Sya’ban (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: In 2019 the government targets the contribution of MSMEs to GDP to increase by 5 percent, To achieve these projections, the government provides support especially related to access to additional funding by issuing a people's business credit policy (KUR), but the facilities of the government are not yet effective enough in encouraging the performance of MSMEs because they are only given to trade businesses, not production businesses. Design/methodology/approach: Research formulation (1) What is the role of Accounting for the Growth of MSMEs?; (2) How is the knowledge and utilization of Fintech by MSMEs? (3) How are the preparations, challenges and opportunities of MSMEs to welcome the indonesian golden 2045 phenomenon? Research methods use qualitative descriptive methods Findings: The results of the study are MSMEs in Lamongan Regency, not much is known about the importance of accounting for business management. Respondents run businesses using only their economic instincts. If you manage to sell a lot means profit, if not sold means loss. Research limitation/implications: Lack of insight and limited understanding of fintech becomes a problem for respondents when getting opportunities for increased turnover but the capital is limited so that the opportunity cannot be utilized. Indonesia gold 2045 phenomenon provides challenges to respondents to adapt to digitalization Practical implications: Capital access is indeed a problem that inhibits MSMEs to spread their wings, including MSMEs who are the object of this research. Paper Type: Research paper